Preparation and optimization of carboxymethyl sago starch hydrogel as a potential carrier for Newcastle disease virus vaccine - Sulta, Normastura (2018)
Carboxymethyl sago starch (CMSS) is an important water-soluble polysaccharide in many applications in food and non-food industries. When crosslinked, CMSS produce three-dimensional polymeric network hydrogel which has the ability to retain a large amount of solution inside its network. Newcastle disease (ND) is a highly contagious disease which causes devastating losses in poultry industries worldwide. This disease is caused by virulent strains of avian paramyxovirus and can be controlled by the used of Newcastle disease virus (NDV) vaccine. However, NDV vaccine is highly sensitive towards high temperature and need a proper storage chain in order to secure its efficacy. In this study, CMSS hydrogel was prepared by dissolving CMSS in HCl solution under vigorous stirring to form hydrogel. This CMSS hydrogel was then used to encapsulate NDV. Four parameters were studied to optimize the preparation of CMSS hydrogel, which were the effect of the percentage of CMSS, concentration of the HCl solution, reaction time and reaction temperature. The percentage of gel content and degree of swelling become the indicators studied in each parameter. 60% of CMSS in 2.0M HCl solution for 12 hours reaction time at room temperature were the optimum conditions for the preparation of CMSS hydrogel which resulted in 70.40 % of gel content with 50.79 (g/g) degree of swelling. The CMSS hydrogel was characterized by using Fourier transform infrared (FT-IR), thermogravimetric analysis (TGA), X-Ray diffraction (XRD) and scanning electron microscopy (SEM). FTIR spectrum of CMSS showed an additional absorption band at 1597 cm-1 indicating the substitution of CH2COO-Na+ group on the starch molecular chain during carboxymethylation. While the spectrum of CMSS hydrogel showed an additional sharp absorption band at 1723 cm-1 indicating that the Na in CMSS being exchanged to H from hydrochloric acid solution. TGA thermograms showed that carboxymethylation reaction shifted the maximum decomposition of sago starch to a lower temperature from 309.57 ºC to 295.33 ºC. However, the presence of crosslinkages in CMSS hydrogel gave better thermal stability when compared to CMSS which gave maximum temperature of decomposition at 330.22 ºC with 60.22 % major weight loss. X-ray diffraction pattern of CMSS showed that the semi-crystalline structure of sago starch completely destroyed after underwent carboxymethylation reaction. SEM image showed distorted and irregular shape of modified sago starch after carboxymethylation. Whereas, CMSS hydrogel showed a spongy surface with empty space called pores in structure and interconnected to each other to form networks. CMSS hydrogel exhibited pH-sensitive behavior as it showed highest swelling at PBS pH 7 but shrank at low pH and acidic solution. Two parameters were carried out in order to investigate the loading and release of encapsulated NDV vaccine in CMSS hydrogel which were the amount of CMSS hydrogel and loading time. 0.02 g of CMSS hydrogel at 30 minutes loading time were the optimum conditions in this study which gave 69.23% of loading and 86.26% of release of NDV vaccine. The stability study of NDV-CMSS hydrogel showed that CMSS hydrogel successfully able to protect the NDV vaccine and retained its stability when stored up to 30 days at room temperature. High thermal properties of CMSS hydrogel with porous structure has allowed NDV vaccine to be trapped inside its three-dimensional matrix. CMSS hydrogel successfully protected the NDV vaccine from deterioration due to high temperature of its surrounding. In conclusion, CMSS hydrogel showed an outstanding result as NDV vaccine carrier which gave ample protection to NDV vaccines. CMSS hydrogel can improve current NDV vaccine storage and delivery without depending on cold chain system.